Sophie’s Defense Mechanism in Her Struggle to Break the Curse in Diana Wynne Jones’ Howl’s Moving Castle - Perwita, Ratnanggana Ausiyyah Mustika (LANTERN (Journal on English Language, Culture and Literature), 2015)
The experience that young people get has an effect to their personality and their problem solving. This is why older people tend to be more mature than the young people. In Diana Wynne Jones’ Howl’s Moving Castle, the main character has a development in her personality through experiences. Her experiences lead her to how she solves her problems while she unconsciously uses defense mechanism. In this case, in this study will be analyzed the characteristic of the main character, Sophie, when she faces a problem while using defense mechanism. The defense mechanism also helps Sophie to break her curse. The study uses psychoanalysis approach to analyze Sophie’s defense mechanism. Her defense mechanism becomes a habit whenever she has problems. Sophie solves her problem not by making it clear, but by reacting toward her fear into its opposite acts (reaction formation). She also refuses to acknowledge the event that happens to her (denial), makes excuse for the things she does (rationalization), and suppresses her unwanted feeling into something pleasant (suppression). Her defense mechanism soon changes her personality without her notification and it helps her reach the goal she thinks she will never get, that is to have an interesting future.